FLOURISHING DITINJAU DARI DUKUNGAN SOSIAL PADA ANGGOTA SAMAPTA BHAYANGKARA POLRES KENDAL - Rahmattullah Yudha Nabila; An Riwi Widyastuti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2023)
This study aims to empirically determine the relationship between social support and flourishing in members of Samapta Bhayangkara Polres Kendal. Data obtained using flourishing scale and social support scale. The sampling technique uses incidental sampling with a total of 128 subjects. Data analysis used Spearman rho, the results of rs value 0.450 with p value = 0.000 (p < 1%), these results indicate there is a very significant positive relationship between social support and flourishing. The categorization results of the flourishing variable are in the high category (99.2%) and the social support variable is also in the high category (94.5%) with the effective contribution of the social support variable to the flourishing variable by 28.6%, the remaining 71.4% of which are influenced by personality, age, gender, and religiosity variables. Keywords : flourishing, social support